(untitled) (MAUSAM, 1959)
A seismometric study of the earthquake of 21 July 1956 in the Rann of Cutch, which caused destruction to life and property at Anjar, has been made. The epicentre and origin time have been determined by the method of least squares and are Lat. 23°20’N, Long 70000’ E and 15h 32m 26S GMT respectively. The shock had a magnitude of 7 and a depth of focus of nearly 13 to 18 km.